Hydrodesulfurization over NiMo Catalysts Supported on Yolk‐shell Silica Materials with Controllable Cavity Size. Issue 39 (19th October 2022) - Yu., Ke; Kong, Weimin; Zhao, Zhen; Duan, Aijun; Kong, Lian; Wang, Xilong
Abstract: Novel yolk‐shell (YS) mesoporous silica materials with different cavity sizes were successfully synthesized. Aluminium was bridged into the yolk‐shell framework of silica by a post synthesis method to improve the acidity of YS, namely Al‐YS. The corresponding NiMo/Al‐YS catalysts were also fabricated and used in the hydrodesulfurization (HDS) reaction of dibenzothiophene (DBT) and 4, 6‐dimethyldibenzothiophene (4, 6‐DMDBT). The NiMo/Al‐YS catalyst with the cavity size of 154 nm (NiMo/Al‐YS‐154) exhibits the superior conversions of DBT (99.2 %) and 4, 6‐DMDBT (96.1 %) at 340 °C, 4.0 MPa, 10 h −1, highest kHDS (13.4×10 −4 mol g−1 h −1 for DBT and 8.9 mol g −1 h −1 for 4, 6‐DMDBT) and highest TOF for DBT (3.7 h −1 ) and 4, 6‐DMDBT (2.3 h −1 ) among the investigated catalysts. The appropriate cavity size of NiMo/Al‐YS‐154 catalyst plays the key role in obtaining its superior HDS catalytic performance. Furthermore, the possible reaction networks of DBT and 4, 6‐DMDBT HDS over NiMo/Al‐YS‐x catalysts were also presented. Abstract : Superior DBT and 4, 6‐DMDBT HDS performance of yolk‐shell structured NiMo/Al‐YS‐154 catalyst due to appropriate cavity size, high structural stability, uniform dispersion of active phases and controllable morphology of MoS2 crystals.